2006
DOI: 10.1519/r-18885.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age on Testosterone Responses to Resistance Exercise and Musculoskeletal Variables in Men

Abstract: This study compared serum total testosterone (TT) and free testosterone (FT) responses of young (20-26 years, n = 8), middle-aged (38-53 years, n = 7), and older (59-72 years, n = 9) men to resistance exercise. We also examined the relationships between testosterone (T) levels and strength, bone mineral density (BMD), and body composition variables for each age group. Subjects were tested for isotonic muscular strength (1 repetition maximum [1RM]), BMD (dual-energy x-ray absorptiometry [DXA]) and body composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 0 publications
0
12
0
3
Order By: Relevance
“…The T:C ratio is related to fatigue management, overtraining potential and a number of physiological variables that can impact performance. For example, the T:C has been associated with lean body mass (LBM), leanness, strength and explosiveness [ 11 , 40 , 41 ]. Testosterone may have dual effects: long-term and short-term.…”
Section: Discussionmentioning
confidence: 99%
“…The T:C ratio is related to fatigue management, overtraining potential and a number of physiological variables that can impact performance. For example, the T:C has been associated with lean body mass (LBM), leanness, strength and explosiveness [ 11 , 40 , 41 ]. Testosterone may have dual effects: long-term and short-term.…”
Section: Discussionmentioning
confidence: 99%
“…These acute elevations have been attributed to plasma volume reductions, adrenergic stimulation, lactate stimulated testosterone secretion, and potential adaptations in testosterone synthesis and/or secretory capacity of the Leydig cells in the testes [ 22 ] . The exercise induced increase in testosterone seems to be dependent upon the amount of muscle mass trained [ 23 ] , intensity and volume [ 24 , 25 ] , nutritional intake [ 26 , 27 ] , age [ 28 ] , gender [ 19 -21 ] , training level [ 29 , 30 ] , and is independent of the individuals absolute level of muscular strength [ 29 ] . To illustrate, large muscle mass movements such as Olympic lifts, deadlifts, and jump squats have been shown to produce substantial increases in testosterone compared with smaller muscle mass exercises (e. g., biceps brachii).…”
Section: Acute Resistance Training ▼mentioning
confidence: 99%
“…It was demonstrated to be high while measuring the serum testosterone, as reported by Herbst et al and confirmed by Kraemer and his team. [113][114][115] While, Izquierdo et al, concluded no change in serum testosterone after (16) weeks of resistance exercise training for a group of middle-aged men which also documented by Nicklas BJ and his colleagues. [116,117] The possible explanation could be related to the age of the participants as more proportion of them are more seniors.…”
Section: Effect Of the Physical Exercise On Associated Risk Factorsmentioning
confidence: 87%